2011
DOI: 10.1186/1742-2094-8-32
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory gene expression in solid glioblastoma microenvironment and in hypoxic stem cells from human glioblastoma

Abstract: BackgroundAdaptation to hypoxia and consequent pro-inflammatory gene expression of prostate and breast carcinomas have been implicated in the progression toward cancer malignant phenotype. Only partial data are available for the human tumor glioblastoma multiforme (GBM). The aim of our study was to analyze the hypoxic and pro-inflammatory microenvironment in GBMs and to demonstrate that in a stem/progenitor cell line derived from human glioblastoma (GBM-SCs), hypoxia activates a coordinated inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(110 citation statements)
references
References 33 publications
2
107
0
1
Order By: Relevance
“…The microenvironment of glioblastoma tumors is characterized by the infiltration of hyperactivated immune cells, which aggravate disease progression. Thus, it can be hypothesized that inhibition of lipid metabolism can also reduce inflammation at tumor sites [88][89][90]. However, the potential side effects of pyrrolidine-2 deter its use in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The microenvironment of glioblastoma tumors is characterized by the infiltration of hyperactivated immune cells, which aggravate disease progression. Thus, it can be hypothesized that inhibition of lipid metabolism can also reduce inflammation at tumor sites [88][89][90]. However, the potential side effects of pyrrolidine-2 deter its use in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies tried to generate a model of GBM and they hypothesized that the GBM tumor mass was a multilayer and the every tumor layer showed distinct characteristic. Pistollato et al [10] describe GSCs distribution according to tissue hypoxic gradient, Piccirilla et al [11] found a different behavior of GSCs derived from distinct tumor areas and Tafani et al [12] demonstrated that the different pro-inflammatory gene expression of diverse tumor areas. The tumor cells are hypoxic, showed high activation of NF-kB and the expression of pro-inflammatory genes were high, the peri-tumor area showed the high activation of NFkB and the pro-inflammatory genes expressions were low, the core region of the tumor was high proliferation capacity and clonogenic ability, the expression of differentiation markers were low and the genetic abnormalities not shared with the tumor periphery.…”
Section: Review Articlementioning
confidence: 99%
“…In response, tumor cells proliferate (ᛏ Ki67) and migrate; and resting stem cells undergo activation and enter the cell cycle. These stem cells are vulnerable to malignant transformation instead of differentiation (156).…”
Section: Tumor Cell Colonies Generated In the Inflammasomesmentioning
confidence: 99%